A216 EXAMINING THE EFFECTS OF GLYPHOSATE EXPOSURE ON THE GUT BACTERIOME AND INFLAMMATION IN A MURINE MODEL OF COLITIS. (26th February 2020) - Barnett, J A; Haskey, N; Quin, C S; Bonnie, R; La Berge, A; Alejandra Verdugo Meza, A; Hart, M; Gibson, D L
Abstract: Background: Canada has the highest incidence of inflammatory bowel disease in the world, which is expected to rise unabated for the next 30 years. Coincidently, Canada is one of the most prolific users of the herbicide glyphosate (tradename Roundup®), with over 25 million kilograms purchased annually. Previous studies examining the effects of glyphosate on the gut bacteriome have used high levels of glyphosate (ranging from 2.5mg – 25mg/kg bw/day) and have yielded conflicting results. Our goal is to examine the effects of dietary levels of glyphosate on the gut microbiome and inflammation in an animal model of colitis. Two environmentally relevant doses were explored: (1) the acceptable daily intake currently set by the Environmental Protection Agency (EPA) (1.75mg/kg bw/day) and (2) North American dose, calculated by a registered dietician using literature values of glyphosate found within food products (0.1mg/kg bw/day.) Aims: 1) To determine if glyphosate exposure influences intestinal permeability 2) To determine if glyphosate exposure influences intestinal inflammation 3) To determine if glyphosate exposure influences colitis onset and severity. We hypothesized that exposure to glyphosate leads to bacterial dysbiosis, increased intestinal permeability and increased severity of colitis in Mucin 2 deficient mice (Muc2 -/- mice). Methods: Upon weaning, Muc2 -/- mice were exposed to glyphosate through their drinking water. Animals were monitored weekly for clinical signs of colitis, including rectal prolapse. Following 12-week glyphosate exposure, intestinal permeability was measured using the FITC-dextran permeability assay. Intestinal inflammation was measured using qPCR and markers relevant to our animal model including REGIIIγ, RELM-β and CLEC-2. Results: Exposure to glyphosate at physiologically relevant levels does not increase intestinal permeability in Muc2 -/- mice, with all groups showing equal levels of FITC-dextran present within their serum. Animals exposed to the EPA dose of glyphosate exhibited earlier onset of colitis symptoms with animals receiving higher clinical scores and displaying an increased rate of rectal prolapse. Animals exposed to the EPA dose also showed a significant increase in CLEC-2 expression. CLEC-2 is a C-type lectin-like receptor expressed by immune cells and platelets and has been implicated in tumor metastasis. Additionally, overexpression of CLEC-2 has been shown to promote pathogen adherence to mammalian cells. Conclusions: Exposure to glyphosate at levels deemed safe by the EPA increases colitis onset and severity in Muc2 -/- deficient animals. Additionally, EPA level glyphosate exposure upregulates CLEC-2 expression which may have implications for tumor development and increased enteropathogenic infections. Funding Agencies: CCCCrowdfunding, NSERC